Observations on the feeding ecology and bioenergetics of the White-faced Whistling Duck in Venezuela - Dallmeier, Francisco Gomez; Rylander, Michael Kent (Wildfowl, 1982)
White-faced Whistling Ducks Dendrocygna viduata are a possible source of protein, suitable for raising in captivity. The nature of the food taken in the wild, and in relation to availability, was determined. Fat content, ash content and combined calorific values of the birds were measured. The maintenance energy for birds held in captivity was investigated, along with their food consumption.